Kontroversi Hukum Bunga Bank: Analisis Fatwa Ulama dalam Ekonomi Islam - Tomi Satria; Khadijah; Widya Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Banking plays a strategic role as an intermediary institution in the economic system, particularly in mobilizing and distributing public funds. However, the implementation of an Interest-based system in conventional banking raises serious concems from the perspective of Islamic economics, as interest is considered to share substantial similarities with riba, which is explicitly prohibited in the Qur'an and Hadith. Differences of opinion among scholars, along with the dominance of conventional banking practices, make bank interest a persistent and widely debated contemporary issue. This study aims to analyze the concept of banking and bank interest from the perspective of Islamic economics and to examine scholarly views and fatwas regarding the legal status of bank Interest. Specifically, it focuses on identifying differences in emphasis among scholarly fatwas and contributes conceptually to contemporary Islamic economic discourse by clarifying the relationship between Sharia principles and modern banking practices. The research employs a qualitative method using a library research approach, drawing on data from the Qur'an, Hadith, classical and contemporary Qur'anic exegesis, fatwas issued by the Indonesian Council of Ulama, Nahdlatul Ulama, and the Muhammadiyah Tarjih Council, as well as relevant Islamic economics literature. The findings indicate that bank interest in conventional banking meets the criteria of riba al-nasiah, which is prohibited in Islam. Islamic banking emerges as an alternative that emphasizes profit-and-loss sharing, justice, and partnership. This study concludes that Islamic banking offers a financial system more consistent with Islamic law and oriented toward public welfare.